Implementasi Metode Experiential Learning Dalam Layanan Bimbingan Dan Konseling Di Sekolah - Nindiya Eka Safitri (STKIP Andi Matappa, 2018)
Availability of qualified human resources and character in an era of MEA become an essential factor because it determines the progress and survival of the nation. HR quality and character can only be established through quality education. Quality education not only includes cognitive but also affective aspects that required a psycho-educational services in the form of guidance and counseling services. Implementation of guidance and counseling services should be oriented towards the development of skills and character for the students. Classical methods of guidance and counseling is usually a lecture which resulted in prolonged verbal symptoms. To overcome these gelaja, the need for full involvement of students in activities / experiences directly in order to achieve the purpose of effective guidance and counseling. Direct experience can be provided by implementing experience-based learning (experiential learning). Knowledge, attitudes and skills are the result of transformation of experience, so the experience is a source of guidance. The success in the implementation of experiential learning method in teaching character through guidance and counseling services is supported by proactive human resources, supportive institutions and facilities and pre means representative.